The Effects of Social Perception on Moral Judgment - Jin, Wen Ying; Peng, Ming (Frontiers in Psychology, 2021)
When people express a moral judgment, others make inferences about their personality, such as whether they are warm or competent. People may use this interpersonal process to present themselves in a way that is socially acceptable in the current circumstances. Across 4 studies, we investigated this hypothesis in Chinese culture, and showed that college student participants tended to associate others’ deontological moral judgments with warmth and utilitarian moral judgments with competence (Study 1, Mage =21.1, SD =2.45; Study 2, Mage =20.53, SD =1.87). In addition, participants made more deontological judgments after preparing to be interviewed for a job requiring them to be in a warm social role, and more utilitarian judgments after preparing for a job requiring them to be in a competent social role(Study 3, Mage =19.5, SD =1.63). This effect held true in moral dilemmas involving different degrees of hypothetical personal involvement, and appeared to be mediated by the perception of others’ expectations(Study 4, Mage =19.92, SD =1.97). The results suggest an important role for social cognition as an influence on moral judgments in Chinese culture.